1998
DOI: 10.1097/00002030-199813000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Declining HIV-2 prevalence and incidence among men in a community study from Guinea-Bissau

Abstract: There are no signs of an epidemic spread of HIV-2 in Bissau even though the HIV-1 prevalence is increasing rapidly. A significant reduction in the male HIV-2 prevalence and incidence rates has resulted in a major shift in the pattern of spread of HIV-2, from being equally distributed to being predominantly a female infection. Currently, older women in particular seem to have a high risk of getting infected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Assuming a shorter duration of HIV-2 infection or a lower Guinea-Bissau is about to decline as observed in some urban settings in this country [5,8], and that this decline may have been hastened by the ongoing HIV-1 epidemic.…”
Section: Sensitivity Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…Assuming a shorter duration of HIV-2 infection or a lower Guinea-Bissau is about to decline as observed in some urban settings in this country [5,8], and that this decline may have been hastened by the ongoing HIV-1 epidemic.…”
Section: Sensitivity Analysismentioning
confidence: 86%
“…In recent years a decline in the prevalence of HIV-2 has been observed in most populations in West Africa including some communities in Guinea-Bissau [5][6][7]. HIV-2 prevalence decreased in men but not in women in a community study from urban Guinea-Bissau between 1987 and 1996 [8]. HIV-2 prevalence has also remained stable in a rural area in Guinea-Bissau (8 .…”
Section: Introductionmentioning
confidence: 99%
“…In general infectious diseases, such as malaria, AIDS, cholera, and tuberculosis are still common and are considered serious threats to public health [9][10][11]. As the access to conventional health care is often difficult, people use both conventional and traditional medicines to improve their health condition.…”
Section: Introductionmentioning
confidence: 99%
“…in the window phase for the antibody assays used. However, given the HIV-2 incidence rates observed in several cohorts in Guinea-Bissau [59][60][61] and the fact that many of the EU individuals had been married for many years, it is not likely that seroincident cases would be a common phenomenon in this study. Moreover, the antibody assays used are very sensitive and previous evaluations have shown that the number of cases missed due to recent seroconversion are limited [50,62].…”
Section: Discussionmentioning
confidence: 93%
“…The group of HIV-2-discordant couples was identified through a population-based prospective cohort project organized in the Bandim and Belem suburbs of Bissau, the capital of Guinea-Bissau [47]. Twenty-nine HIV-2-exposed but HIV-seronegative (EU) people were enrolled in this study.…”
Section: Study Groupsmentioning
confidence: 99%